Bimetallic Pd–Pt alloy nanocluster arrays on graphene/Rh(111): formation, stability, and dynamics. Issue 33 (8th August 2018) - Düll, Fabian; Bauer, Udo; Späth, Florian; Bachmann, Philipp; Steinhauer, Johann; Steinrück, Hans-Peter; Papp, Christian
Abstract : We investigated the formation, stability, and dynamics of graphene-supported Pd–Pt alloy nanoclusters with in situ HR-XPS with CO as a probe molecule. Abstract : Alloy catalysts have, in many cases, superior properties compared to their single metal counterparts. To gain deeper insights, we used graphene-supported bimetallic nanocluster arrays as a model system. We investigated the site occupation and the dynamic behavior of the metal distribution during adsorption and thermal treatment of CO layers on PdPt alloy nanocluster arrays supported on the graphene/Rh(111) Moiré. We find that the adsorption of CO combined with heating to 550 K leads to a rearrangement of the surface atoms, resulting in all the edge sites of the nanoclusters being occupied by Pd atoms. At the same time, Pt gets enriched at the surface.